A previously unknown Argonaute 2 variant positively modulates the viability of melanoma cells - Linck-Paulus, Lisa; Meißgeier, Tina; Pieger, Katharina; Horn, Anselm; Matthies, Alexander Oliver; Fischer, Stefan; Meister, Gunter; Sticht, Heinrich; Kappelmann-Fenzl, Melanie; Boßerhoff, Anja Katrin (Cellular and Molecular Life Sciences, 2022)
In malignant melanoma, a highly aggressive form of skin cancer, many microRNAs are aberrantly expressed contributing to tumorigenesis and progression. Further, deregulation of microRNA processing enzymes, like the miRNA-binding protein Argonaute 2, significantly impacts microRNA function. This study characterizes a novel splice variant of Argonaut 2, AGO2-ex1/3. AGO2-ex1/3 is substantially expressed in different melanoma cell lines and patient-derived tissue samples. It is a mature mRNA, which is translated into an N-terminally truncated Argonaute 2 protein form. Molecular dynamics simulations show that the PAZ, MID, and PIWI domain largely retain their structure in AGO2-ex1/3 and that the truncation of the N-terminus leads to an increased interdomain flexibility. Expression of AGO2-ex1/3 provides a survival advantage for melanoma cells while the knockdown causes significantly reduced proliferation and increases apoptosis. RNA-sequencing revealed that in cells lacking AGO2-ex1/3 expression many miRNA target genes are deregulated, implicating a considerable role of AGO2-ex1/3 for miRNA function. This study inaugurates insights into an important role of a so far unknown splice variant of Argonaute 2 for the miRNA pathway as well as the mechanisms which drive growth and survival of melanoma cells. This knowledge provides the basis for potential new promising therapeutic targets focusing on small RNA-mediated gene regulation in melanoma.
CRIS-Team Scopus Importer:2022-08-19
Keywords: Alternative splicing; Argonaute 2; Melanoma; miRNAs

NRN1 interacts with Notch to increase oncogenic STAT3 signaling in melanoma - Devitt, Lucia; Westphal, Dana; Pieger, Katharina; Schneider, Nadja; Boßerhoff, Anja Katrin; Kuphal, Silke (Cell Communication and Signaling, 2024)
Background: Melanoma is a highly heterogeneous cancer, in which frequent changes in activation of signaling pathways lead to a high adaptability to ever changing tumor microenvironments. The elucidation of cancer specific signaling pathways is of great importance, as demonstrated by the inhibitor of the common BrafV600E mutation PLX4032 in melanoma treatment. We therefore investigated signaling pathways that were influenced by neurotrophin NRN1, which has been shown to be upregulated in melanoma. Methods: Using a cell culture model system with an NRN1 overexpression, we investigated the influence of NRN1 on melanoma cells’ functionality and signaling. We employed real time cell analysis and spheroid formation assays, while for investigation of molecular mechanisms we used a kinase phosphorylation kit as well as promotor activity analysis followed by mRNA and protein analysis. Results: We revealed that NRN1 interacts directly with the cleaved intracellular domain (NICD) of Notch1 and Notch3, causing a potential retention of NICD in the cytoplasm and thereby reducing the expression of its direct downstream target Hes1. This leads to decreased sequestration of JAK and STAT3 in a Hes1-driven phosphorylation complex. Consequently, our data shows less phosphorylation of STAT3 while presenting an accumulation of total protein levels of STAT3 in association with NRN1 overexpression. The potential of the STAT3 signaling pathway to act in both a tumor suppressive and oncogenic manner led us to investigate specific downstream targets – namely Vegf A, Mdr1, cMet - which were found to be upregulated under oncogenic levels of NRN1. Conclusions: In summary, we were able to show that NRN1 links oncogenic signaling events between Notch and STAT3 in melanoma. We also suggest that in future research more attention should be payed to cellular regulation of signaling molecules outside of the classically known phosphorylation events. Graphical Abstract: (Figure presented.).
CRIS-Team Scopus Importer:2024-05-10
Keywords: Melanoma; Notch; NRN1; STAT3

Translocation of Distinct Alpha Synuclein Species from the Nucleus to Neuronal Processes during Neuronal Differentiation - Pieger, Katharina; Schmitt, Verena; Gauer, Carina; Gießl, Nadja; Prots, Iryna; Winner, Beate; Winkler, Jürgen; Brandstätter, Johann Helmut; Xiang, Wei (Biomolecules, 2022)
Alpha synuclein (aSyn) and its aggregation are crucial for the neurodegeneration of Parkinson's disease (PD). aSyn was initially described in the nucleus and presynaptic nerve terminals. However, the biology of nuclear aSyn and the link of aSyn between subcellular compartments are less understood. Current knowledge suggests the existence of various aSyn species with distinct structural and biochemical properties. Here, we identified a C-terminal-targeting aSyn antibody (Nu-aSyn-C), which has a high immunoaffinity towards aSyn in the nucleus. Comparing the Nu-aSyn-C antibody to aSyn antibodies developed against phosphorylated or aggregated forms, we observed that nuclear aSyn differs from cytosolic aSyn by an increased phosphorylation and assembly level in proliferating cells. Employing Nu-aSyn-C, we characterized aSyn distribution during neuronal differentiation in midbrain dopaminergic neurons (mDANs) derived from human-induced pluripotent stem cells (hiPSCs) and Lund human mesencephalic cells, and in primary rat hippocampal neurons. We detected a specific translocation pattern of aSyn during neuronal differentiation from the nucleus to the soma and finally to neuronal processes. Interestingly, a remarkable shift of Nu-aSyn-C-positive species towards neurites was detected in hiPSC mDANs from a PD patient carrying aSyn gene duplication. Together, our results reveal distinct nuclear and cytosolic aSyn species that redistribute during neuronal differentiation-a process that is altered in PD-derived neurons.
CRIS-Team WoS Importer:2022-09-09